PENGEMBAGAN PRODUK OLAHAN KOMODITAS JERUK MELALUI KEGIATAN PENGABDIAN MASAYARAKAT PADA KELOMPOK TANI NGUDI REJEKI, DI DESA PECORO, JEMBER - Setyohadi, Dwi Putro Sarwo; Kusumaningtyas, Rizky Nirmala; Ali , Fandyka Yufriza; Firgiyanto , Refa (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Siam’s oranges is one of the leading horticultural commodities in Jember Regency, East Java. With a high level of demand, both in the local and national markets, Siamese orange has great potential to be developed as the main source of income for farmers. The target of the Community Service activity is to increase the knowledge of partners in this case the Ngudi Rejeki farmer group regarding knowledge about the nutritional content of oranges and product diversification/product development of the Siamese orange commodity. Based on the results of the extension activities that have been carried out, it can be concluded that the participants, namely the Ngudi Rejeki farmer group, have succeeded in making product diversification in the form of jam and orange juice